Environmental and genetic effects on udder characteristics and milk production in Damascus goats - Mavrogenis, Andreas; Lysandrides, P.; Roushias, A.; Papachristoforou, Christakis (My University, 1989)
A total of 829 records collected at three experimental farms (ARI, Athalassa and Orites) from 1979 to 1982 was studied for environmental and genetic influences on udder characteristics and milk production in Damascus goats. All udder traits were recorded following weaning (70 ± 3 days) concurrently with the first milk recording (7± 3 days after weaning). Most traits were significantly rekated to flock except milking ease, test-day milk and 90-day milk yield. Year effects were small (P>0.05) for udder depth, udder floor, udder quality, milking ease and total milk yield. Season significantly affected udder depth and total milk production. Lactation number had a significant effect on all traits except udder floor, udder quality and milking ease. Udder floor was significantly related to milk production, while udder quality and milking ease had no effect. Most heritability estimates, except for udder quality (0.03 ± 0.09), were moderate to high. Test-day milk yield (0.31 ± 0.11) and udder floor (0.22 ± 0.11) had moderately low heritability estimates, while teat length and diameter were highly heritable (from 0.55 ± 0.13 to 0.77 ± 0.14). Heritability estimates for 90-day and total milk production were 0.52 ± 0.13 and 0.46 ± 0.12, respectively. Udder circumference and udder depth (traits that describe the volume of the udder) were moderately heritable. Genetic association of udder circumference before milking with milk production was moderately high. Phenotypic correlation among the above traits was positive and also moderately high.